Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acschemneuro.9b00527
|View full text |Cite
|
Sign up to set email alerts
|

Role of α-Synuclein Regions in Nucleation and Elongation of Amyloid Fiber Assembly

Abstract: α-Synuclein is an intrinsically disordered protein whose aggregation in the form of amyloid fibers is directly implicated in Parkinson's disease and other neurological disorders. α-Synuclein is composed of three different regions. The central region (61−95), called NAC, is responsible for protein fibrillation. The N-terminal region (1−61) has some helical propensity and can be divided into H1 (1−31) and H2 (32−61), while the highly acidic C-terminal region (96−140) is completely disordered. It has been postula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 27 publications
3
28
0
Order By: Relevance
“…αS is a 140 amino acid protein containing three regions; lipid binding N-terminal domain (NTD), an aggregation-prone non-amyloid component (NAC) middle region, and an intrinsically disordered, charged C-terminal domain (CTD). NAC and a part of NTD are the primary regions responsible for aggregation, while CTD seems to play an inhibitory role for this process [28,29]. On the other hand, TDP-43 is a 414 amino acid containing ribonucloprotein protein with an N-terminal domain, two RNA recognition motifs (RRMs), and a disordered prion-like C-terminal domain (PrLD) containing low complexity sequences [30].…”
Section: Introductionmentioning
confidence: 99%
“…αS is a 140 amino acid protein containing three regions; lipid binding N-terminal domain (NTD), an aggregation-prone non-amyloid component (NAC) middle region, and an intrinsically disordered, charged C-terminal domain (CTD). NAC and a part of NTD are the primary regions responsible for aggregation, while CTD seems to play an inhibitory role for this process [28,29]. On the other hand, TDP-43 is a 414 amino acid containing ribonucloprotein protein with an N-terminal domain, two RNA recognition motifs (RRMs), and a disordered prion-like C-terminal domain (PrLD) containing low complexity sequences [30].…”
Section: Introductionmentioning
confidence: 99%
“…α-Syn C-terminal truncation enhances aggregation in vitro [ 16 , 17 , 46 , 47 ] and in vivo [ 48 , 49 , 50 ]. The protective role proposed for the charges at the C-terminus via long-range intramolecular interactions is lost upon truncation, which favors aggregation [ 18 , 51 , 52 , 53 , 54 ]. C-terminal charges also seem to play an important role after fibril formation, generating an interfibrillar electrostatic repulsion.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that truncation strongly influences α-syn aggregation and prion-like pathogenicity [ 14 , 17 , 18 ], very little is known about the effect of this PTM on aggregate clearance. α-Syn fibrils and oligomers are disassembled by the human disaggregase, a chaperone system composed of three proteins: Hsc70 (a constitutively expressed member of the Hsp70 family), DnaJB1 (a representative of the class B Hsp40 or J-protein family) and Apg2 (a nucleotide exchange factor of the Hsp110 family) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…α-syn can be divided into three different domains ( Figure 1 A): an N-terminal amphipathic region (residues 1–60) which presents five conserved lysine-rich repeats, the central non-amyloid-β component (NAC) domain (residues 61–95) which forms the core of α-syn amyloid fibrils, and the unstructured C-terminal acidic region (residues 96–140) [ 12 ]. While the first 37 residues of the N-terminal region and the C-terminal domain hinder nucleation, the second portion of the N-terminal domain favors it [ 13 ]. The structure of α-syn is highly dependent on environmental factors and the complexation state.…”
Section: Introductionmentioning
confidence: 99%